(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Parkinson’s disease can be presented as non-motor clinical features. Objective: The purpose of the present study was to observe the demographic and non-motor clinical profiles of Parkinson’s disease patients. Methodology: This descriptive cross-sectional study was carried out in the Department of Neurology at Mymensingh Medical College, Mymensingh, Bangladesh from January 2009 to December 2010 for a period of two(02) years. PD patient presents with both motor and non-motor symptoms. NMS has variable presentations like sensory, autonomic, psychiatric and sleep disorder. Parkinson’s disease patients were diagnosed clinically. Each patient was assessed by a standard questionnaire, including sensory, autonomic, psychiatric and sleep disorder symptoms. Result: A total number of51 Parkinson’s disease patients were recruited for this study. Mean (±SD) age of male and female were 57.51±7.1 years and 60.00±10.2 years. Out of the 51 patients, 58.8% patients had sensory, 72.5% patients had autonomic, 47.1% patients had neuro-psychiatric and 66.7% patients had sleep disturbance symptoms. The most frequent sensory symptoms were akathisia 47.1%, diffuse pain 37.3%,and tightening sensation 27.5%. The most frequent autonomic symptoms were excessive sweating 54.9%, palpitation 35.3%, oral dryness 33.3%. The most frequentneuro-psychiatric symptoms were fatigue 56.8%, anxiety 45.1%, and depression 23.5%. The most frequent sleep disorders were insomnia 54.9%, day time sleepiness 11.8% and restless leg syndrome 9.8%. Conclusion: In conclusion elderly male rural people are commonly presented with PD presented with akathisia, diffuse pain, excessive sweating, palpitation, oral dryness, fatigue, anxiety and depression Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 123-128